2013
DOI: 10.1155/2013/524820
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and the Risk of Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder that accounts for the major cause of dementia, and the increasing worldwide prevalence of AD is a major public health concern. Increasing epidemiological studies suggest that diet and nutrition might be important modifiable risk factors for AD. Dietary supplementation of antioxidants, B vitamins, polyphenols, and polyunsaturated fatty acids are beneficial to AD, and consumptions of fish, fruits, vegetables, coffee, and light-to-moderate alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
171
0
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(183 citation statements)
references
References 170 publications
(162 reference statements)
1
171
0
11
Order By: Relevance
“…Overall, Alzheimer's disease is a growing major public health concern with profuse socioeconomic impact 19 .…”
Section: Alzheimer's Disease: the Dimension Of The Problemmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, Alzheimer's disease is a growing major public health concern with profuse socioeconomic impact 19 .…”
Section: Alzheimer's Disease: the Dimension Of The Problemmentioning
confidence: 99%
“…These disease-modifying factors have been object of much research in recent years given that interventions that alter their course constitute potential preventive measures 19,25 . Therefore, when motivated and supported by health professionals, individuals can use lifestyle options to influence their late-life cognitive performance and risk of brain disorders 10,15,26 .…”
Section: Alzheimer's Disease Risk and Protective Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studying this effect in more detail could also help to understand the potential role of alcohol in the pathogenesis of different health outcomes, which are closely related to RBD. For example, previous studies found that moderate alcohol consumption was associated with a lower risks of cardiovascular disease7, 8 and cognitive impairment (and Alzheimer's disease) 9, 10. A large cohort study on Parkinson disease (PD) also reported that different types of alcoholic beverages might have different impacts on PD risk 11.…”
Section: Introductionmentioning
confidence: 99%